Kesesuaian Warna GTC Keramik-Logam Terhadap Gigi Asli Pada Pasien Di RSGM Prima Medan - Azizah, Nur; Aziz, Helmi; Sinamo, Sopan; Sim, Mellisa (Syntax Idea, 2020)
The suitability of metal-ceramic fixed partial denture with the adjacent teeth is something that must be concidered in prosthodontics. To produce a good color match there are 3 factors : the color determination factor in the clinic, the communication between the operator and the laboratory, and the color adjustment factor in the laboratory. Many studies have been done but there are still many colors of metal-ceramic fixed partial dentures that do not match the adjacent teeth. The main purpose of this study to find out the result of color matching of metal-ceramic fixed partial denture to adjacent teeth in patient at RSGM Prima Mean. This research is a descriptive observational with cross- sectional design. The results showed that of the 50 patients who used metal- ceramic fixed partial denture in RSGM Prima Medan there were 13 patients (26%) who had the colors that match adjacent teeth and 37 patients (74%) who had colors that did not match the adjacent teeth. The conclusion of this study was that of 37 patients (100%) who had the colors of metal-ceramic fixed partial denture did not match with adjacent teeth, 26 patients (70.3%) errors occurred during color determination in the clinic, 7 patients (18.9%) errors in communication between the operator and the laboratory, and there were errors when determining color in the laboratory as many as 4 patients (10.8%).